Information technology project management - Schwalbe, Kathy, author (Australia : Cengage Learning, 2014)
Discover exciting "behind-the-scenes" opportunities and challenges in technology today with Schwalbe's unique INFORMATION TECHNOLOGY PROJECT MANAGEMENT, 7E. This one-of-a-kind book demonstrates the principles distinctive to managing information technology that extend well beyond standard project management requirements. No book offers more up-to-the minute insights and software tools for information project management success, including updates that reflect the latest PMBOKʼ Guide, Fifth edition. The book weaves today's theory with successful practices for an understandable, integrated presentation that focuses on the concepts, tools, and techniques that are most effective today. Information technology project management is the only book to apply all ten project management knowledge areas to technology projects. You master skills in project integration, scope, time, cost, quality, human resource, communications, risk, procurement, and stakeholder management as well as all five process groups-initiating, planning, executing, monitoring and controlling, and closing. Intriguing examples from familiar companies featured in today's news, a new Agile case, opportunities with MindView 4 Business software, and a new chapter on project stakeholder management further ensure you are equipped to manage information technology projects with success